2011
DOI: 10.1590/s0104-42302011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Estenose carotídea e cirurgia de revascularização miocárdica

Abstract: CS showed a high prevalence in the study sample and together with CRF was a mortality independent factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…About 67.1% (51) of the patients with a stenosis ≥50% were male. [ 10 ] Mahmoudi et al . performed carotid duplex ultrasound in 878 patients before isolated CABG and found that 13% had a carotid stenosis >75%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 67.1% (51) of the patients with a stenosis ≥50% were male. [ 10 ] Mahmoudi et al . performed carotid duplex ultrasound in 878 patients before isolated CABG and found that 13% had a carotid stenosis >75%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 16 ] Carotid murmur was detected in 15.6% (6 patients) of the patients who has CAS in our study while da Rosa and Portal found it to be 35.5% (27 patients). [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…There is a high association between PAD, coronary artery disease and carotid artery disease, which predisposes these patients to an increased risk of myocardial infarction, ischemic stroke and vascular death, with the relative risk of mortality increased by three times for all causes, and by six times for vascular death, as seen by Durazzo et al [ 18 ] . According to Rosa & Portal [ 19 ] , carotid disease increases by four times the risk of perioperative stroke. PAD is more prevalent after the fourth decade of life, with the risk increasing two to three times every 10 years, and is associated with the following cardiovascular risk factors: smoking, DM, hypertension, and dyslipidemia [ 18 , 20 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of stroke after CABG in patients with severe carotid occlusive disease is high, such timely identification of high-risk patients is one of the advantages. [ 10 11 ]…”
Section: Discussionmentioning
confidence: 99%